Surgical Management of Paraganglioma of the Organ of Zuckerkandl with Combined Resection of the Aorta and Inferior Vena Cava with Bifurcation: A Case Report - Shalini Shree Krishnamurthy; Saravanan Moorthy; Krishna Muralidharan; Anand Raja (Vascular Specialist International)
Paragangliomas are rare neuroendocrine tumors that frequently arise in the organ of Zuckerkandl (OZ). Surgical resection remains the cornerstone of treatment. Although vascular resection and reconstruction have been reported in a few cases, no prior reports have documented the simultaneous resection of both the aorta and inferior vena cava (IVC), along with their bifurcation. We present the case of a 50-year-old man with a large paraganglioma of the OZ, successfully managed through combined resection of the aorta, IVC, their bifurcation, and the psoas muscle. Dacron Y-grafts were used to reconstruct both the aorta and IVC. This case underscores the importance of detailed anatomical knowledge of major vessels, meticulous vascular control, and the technical intricacies of vascular reconstruction. We emphasize the significance of comprehensive perioperative management and provide a literature review on en bloc vascular resection for paraganglioma, offering insights into current surgical practices and outcomes.